2008
DOI: 10.1016/j.trstmh.2008.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Two Leishmania species circulating in the Kaleybar focus of infantile visceral leishmaniasis, northwest Iran: implications for deltamethrin dog collar intervention

Abstract: Leishmania infantum is the causative agent of infantile visceral leishmaniasis (IVL) in the Mediterranean Basin and, based on isoenzyme typing of a few isolates from patients and domestic dogs, this parasite was considered to predominate in the Kaleybar focus of IVL in northwest Iran. However, in the current investigation only one out of five sandfly infections was found to be L. infantum, based on PCR detection and sequencing of parasite internal transcribed spacer (ITS) rDNA infecting Phlebotomus perfiliewi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…in sand flies could be successfully detected and identified by PCR methods. 14,14,30 In our study, although the incidence rate of VL was not high in 2006 (the number of reported cases in the region had decreased from more than 100 cases in 2000 to only 14 cases in 2006), we detected Leishmania spp. or Leishmania -like spp.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…in sand flies could be successfully detected and identified by PCR methods. 14,14,30 In our study, although the incidence rate of VL was not high in 2006 (the number of reported cases in the region had decreased from more than 100 cases in 2000 to only 14 cases in 2006), we detected Leishmania spp. or Leishmania -like spp.…”
Section: Discussioncontrasting
confidence: 55%
“…Phlebotomus perfeliewi transcaucasicus was found the only vector of the causative agent of VL found in that region. 30 Phlebotomus perfiliewi perfiliewi , the sister subspecies of P. perfeliewi transcaucasicus , has been identified as a vector of VL/CL caused by L. infantum in Mediterranean countries such as Italy and Algeria. [31][32][33][34] In our study, we also found Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…P. perfiliewi transcaucasicus and P. kandelakii have been reported as the proven vectors of VL in Azarbaijan-e-sharqi and Ardabil [21], [22]. Parvizi et al 2008 [23] and Sanei Dehkordi et al 2011 [24] have reported P. perfiliewi as the proven vector of VL in Kaleybar and Bileh Savar counties.…”
Section: Introductionmentioning
confidence: 99%
“…In areas where canine leishmaniasis is endemic, up to 25% of the dogs are infected, most of them not presenting clinical signs (Gavgani et al 2002, Parvizi et al 2008. Cases of feline Leishmania infection have not yet been documented in Iran; therefore, this study aimed at evaluating Leishmania infection in cats in areas where VL is endemic in Iran.…”
Section: Introductionmentioning
confidence: 99%